Regional cooperation in addressing food security issues in Southeast Asia: Malaysian perspectives - Bakri Mat; Zarina Othman (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
Food insecurity has long been classified as one of the major threats to human wellbeing. In the field of international relations, the concept of human security as highlighted by the UNDP is viewed as an alternative to the mainstream state-centric paradigms designed to tackle the food insecurity issue. In this vein and to address this issue in Southeast Asia, various initiatives and efforts have been taken at regional levels through ASEAN but due to various reasons the desired outcomes have yet to be achieved. This article examines the effectiveness of ASEAN food security framework of cooperation and elucidates the factors that encourage Malaysia to support the existing mechanism. It is based on descriptive content analysis utilising primary data from field interviews and related secondary data. The findings show that in addition to the poor commitment of member states, conflicting national interests between member states are among the major factors that have hindered the regional cooperation framework from effectively addressing the food security issue, as well illustrated by the 2007/2008 episode of food crisis experienced by the region. In spite of the relative ineffectiveness, Malaysia continues to support the regional framework because it does provide a backup strategy in the event of domestic emergencies. Nevertheless, while working for more effective participations of member countries, the Malaysian government would do well to pay more serious attention to the nation’s domestic food production sector in the interest of the people.